Cash Flow Management Challenges Faced by Small Family-Owned Businesses in Zimbabwe - Mufaro Dzingirai; Rodgers Ndava (Bina Nusantara University, 2022)
Cash flow management has increasingly become a concept of interest in the context of small family-owned businesses in recent years. It is worth noting that the growth rate of family-owned businesses has continued to rise in recent years. The research aimed to explore the cash flow management challenges faced by small family-owned businesses in Zimbabwe. The research philosophy of constructivism was employed as it was more appropriate for explorative qualitative study. With the adoption of a qualitative approach, in-depth interviews and Focus Group Discussions (FGDs) were conducted. The research was conducted on 12 owners of small family businesses from diverse sectors of the economy. Then, thematic analysis was applied to analyze data from in-depth interviews and FGDs. The results show that small family-owned businesses face a myriad of cash flow management challenges. Those challenges are poor payables and receivables management, inadequate cash balances, lack of financial experts, absence of cash budgets, bad debts, cash instability, and Unhu/Ubuntu culture. The research outcomes have practical implications for financial institutions and governments when offering financial management capacity-building workshops. Interestingly, the management of family businesses can make evidence-based decisions related to cash management practices and cash operating cycles. The research can immensely enrich the extant mainstream literature on the family business.